Hamlet (Un-)Masked: SPAC’s Hamlet under COVID-19 Restrictions - Tsukamoto, Tomoka; Motohashi, Ted (Multicultural Shakespeare: Translation, Appropriation and Performance, 2024)
One of the reasons why Shakespeare’s Hamlet, as a play representing the essential problematics of Western Modernity, is still relevant today, is that it contains the cultural dynamics that ranges over issues around colonialism, patriarchy, and individual identities, all of which have been causes and consequences of the Western Modernity. More specifically, in the current context of the declining Western hegemony, symbolized by regional military conflicts and environmental degradation, among other crises, the urgency to freshly produce and interpret this play seems to be increasing. This essay attempts to question the significance of staging Hamlet today by examining Satoshi Miyagi’s version of the play at the Shizuoka Performing Arts Center (SPAC) in 2021 during the COVID-19 pandemic, and through its analysis, we aim to reflect how Hamlet, while characterizing Western Modernity, harbors the potential to critique its essence.